Rituales y Tradiciones: Un análisis etnográfico de las festividades religiosas del barrio San Miguel de Tapi- Riobamba. - Colcha Vallejo, Evelyn Dayana (2025)
This research analyzes the religious festivities of the San Miguel de Tapi neighborhood in Riobamba from an ethnographic perspective, aiming to understand the importance of rituals and traditions in the community's cultural identity. The overall objective is to analyze these festivities ethnographically, considering their historical, symbolic, and social aspects. To explore this proposal, we use a qualitative framework that combines participant observation, semi-structured interviews, and documentary analysis. This method enables the collection of highly detailed and precise information on the practices, symbols, and meanings that shape the celebrations. The findings show that these festivities not only reject social cohesion but also act as vehicles for the transmission of values, historical memory, and cultural resistance to the effects of globalization and contemporary social changes. Furthermore, transformations in rituals are evident due to factors such as migration and modernization, which give rise to new desires for their conservation. This study highlights the importance of religious ceremonies as a tangible element of the cultural heritage of the San Miguel de Tapi neighborhood and the urgent need to implement strategies for their conservation. The results provide valuable information for researchers in the field of cultural studies, as well as for heritage management and public decision-making in cultural preservation